Resistant force model of viscous damping wall considering influence of loading frequency. (15th April 2018) - Sun, Feifei; Wu, Tanye; Mo, Gang
Highlights: Direct data-fitting leads to erroneous hysteretic curves of viscous damping walls. A unified model considering frequency effect is established with five assumptions. The varying frequency effect is captured by a data-fitting velocity exponent. The steady state behavior is characterized by a constant velocity exponent. The model is validated with satisfactory accuracy in predicting test results. Abstract: Due to the heterogeneity and velocity-dependency of viscous fluid, it's quite difficult to simulate the dynamic behavior of viscous damping wall (VDW). The existing formulae for resistant forces need different parameter values for different loading frequencies. This may lead to large errors in resistant forces of VDWs subjected to an earthquake with large frequency change. A small-scale shaking table test and a large-scale dynamic actuator test were performed to investigate the influence of loading frequency, showing that direct data fitting with a single set of parameter values for different frequencies will lead to erroneous hysteretic cycles. Based on experimental results, five assumptions were proposed and thereafter a unified model was developed considering the influence of loading frequency by means of introducing the effect of loading history. The proposed model was validated with satisfactory accuracy in predicting the test results.